The study of Judaism: authenticity, identity, scholarship - Hughes, Aaron W. (SUNY Press, 2013)
Authenticity, identity, scholarship -- Encountering tradition: the search for a Jewish essence -- Imagining Judaism: scholar, community, identity -- Take ancient Judaism for example: five case studies -- Private foundations encounter Judaism -- Future prospects